Juridical Review of the Assembly’s Recommendation Required for Civil Suit Administration from the Human Rights Perspective - Dody Novizar Mardyansyah; Anak Agung Gede Duwira Hadi Santosa (Journal of Law, Politic and Humanities, 2025)
The enactment of the health law in 2023 will have a fundamental impact on the development of health law, in which the Article 308 (2) implies for the civil liability, with the rules that patients who are harmed are required to request a letter of recommendation from the assembly. Meanwhile, Human Rights Law No: 39 of 1999 clearly stated that those who feel that their interests have been harmed can directly file a civil claim/lawsuit to a court institution. Thus, there is a conflict of norms between the two laws and regulations which has an impact in the legal uncertainty. For that reason an in-depth analysis of the issue was carried out. Axiologically this research was conducted aiming  for finding out the essence of the recommendation letter issued by the assembly. This research uses doctrinal research methods. The research results show that the requirement to request a letter of recommendation from the assembly as a condition for submitting civil legal action is a contradiction to the principles of basic rights (HAM) as mentioned in Law 39 of 1999